Scientific management school problem’s evolution (based on highly ranked Russian scientific journals) - I. K. Bitkina (Вестник университета)
The aim of the study is to identify and substantiate the features of Russian management science development at the present stage. This aspect is significant both for Russian science, and for management practice. For the first one, it is important to systematise and formulate directions for the application of the most effective research methods of various problem management’s areas. For practice, this is due to the possibility of adapting conceptual recommendations in the activities of a particular economic entity. The analysis was based on highly ranked publications. The information base consisted of 38 articles from five peer-reviewed scientific journals included in the Russian Science Citation Index (RSCI) database, and international citation databases. The review of methodology and methods used in domestic research on management issues has been carried out. The methodological basis of the study was the evolutionary approach: the stages of the evolution of the methodology and the problems of research have been shown. Possible promising directions of Russian management science in the future were outlined. The features of the methodology and methods for research the Russian management science have been substantiated, by of these a three basic problem areas have been identified. The results obtained can be used by domestic scientists in determining the management-oriented research methodology.